A methodology for gamifying of the educational process - Zamyatina, Oxana; Mozgaleva, Alena; Cabral, Pedro da Costa Brito; Mozgaleva, Polina (Proceedings of 2018 IEEE Global Engineering Education Conference (EDUCON), 17-20 April, 2018, Santa Cruz de Tenerife, Canary Islands, Spain)
Abstract-In this research study, the authors designed, proposed, tested, and partially re-searched a methodology for the gamification of academic disciplines through the example of the Elite Engineering Education (EEE) program in Tomsk Polytechnic University (TPU). Gamification implies augmenting the process of training in academic disciplines by introducing game elements that motivate students to gain new knowledge, develop their competencies, and, in the end, improve a university graduate's knowledge and skill levels